Pre-service English teachers’ identity construction, and its manifestation in the teaching practices during the practicum cycle (2024)
ABSTRACT: This study explores the relationship between pre-service teachers’ identities and their teaching practices during their practicum cycle through narrative inquiry. Drawing on Mosquera-Pérez and Losada-Rivas (2021), it could be concluded that teachers’ identities were divided into four categories: historical, professional, sentimental and personal. In fact, it could be deduced that these identities influenced the teaching practices that are planning, teaching, interacting with students, and reflecting about what is being taught and who the teacher is and wants to be. The participants of this study were its two authors. Data was collected through autobiographies and anecdotes about different relevant moments that could lead to an answer of how the participants built their identities as pre-service English teachers and how they portraited them in their teaching practices during the practicum cycle. It was found that those four types of identities were present in their stories and led them to constant reflections about what they were doing as pre-service teachers and who they wanted to become after the practicum cycle was over.